Словники як джерела унормованої та застандартизованої комп'ютерної термінології (90-ті роки XX ст. - перші десятиліття XXI ст.) - Ментинська, І. Б.; Наконечна, Г. В. (Дніпровський національний університет імені Олеся Гончара, 2019)
The article aims to analyse lexicographical processes in Ukrainian computer terminology in the post-Soviet period. Accordingly, the objectives of the article are as follows: 1) to describe the dynamics of the output of lexicographical works fixing computer terminological units; 2) to characterize the types of terminological works representing the studied lexemes; 3) to predict the development of terminographic processes in the computer field. The relevance of the research stems from the very object of the analysis: computer area is in the process of dynamic development, requiring therefore thorough study. The scientific novelty of the research lies in a systematic approach to the analysis of the dynamics of terminological processes in the computer field in the post-Soviet period. Ukrainian computer terminological vocabulary is properly represented in the terminological works. Specialized dictionaries are a high-quality tool that captures the main achievements of the theory and practice of the studied terminological system, systematizing various data on terminological units both for users and for solving new various tasks. Creation of electronic versions of already compiled dictionaries and electronic computer dictionaries is getting more and more popular, which contributes to a comprehensive lexicographic processing of terminology.
Keywords: terminology; lexicography; Ukrainian computer terminology; types of dictionaries; fixed terminological units